2018
DOI: 10.3389/fphar.2018.00957
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 and Rd Remarkably Inhibited the Hepatic Uptake of Ophiopogonin D in Shenmai Injection Mediated by OATPs/oatps

Abstract: Shenmai injection (SMI) is derived from traditional Chinese herbal prescription Shendong yin and widely used for treating cardiovascular diseases. Ophiopogonin D (OPD) is one of the main active components of SMI. The hepatic uptake of OPD is mediated by organic anion-transporting polypeptides (OATPs/oatps) and inhibited by some other components in SMI. This study aimed to identify the active components of SMI responsible for the inhibitory effects on hepatic uptake of OPD in rats and explore the compatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…OATPs are multispecific transport proteins, which can transport cations, anions and neutral compounds in cells, and plays an important role in drug absorption, distribution and excretion in vivo ( Obaidat et al, 2012 ; Liu et al, 2018 ). Shi found that OATP mediates the selective accumulation of the heptamethine dye IR-780 in tumor cells ( Zhang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…OATPs are multispecific transport proteins, which can transport cations, anions and neutral compounds in cells, and plays an important role in drug absorption, distribution and excretion in vivo ( Obaidat et al, 2012 ; Liu et al, 2018 ). Shi found that OATP mediates the selective accumulation of the heptamethine dye IR-780 in tumor cells ( Zhang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Q9NPD5, also known as OATP1B3, is an anion transporter. It has been proven that the hepatic uptake of OPD and OPD′ is mediated by organic anion-transporting polypeptides (OATPs) [ 46 48 ]. This report, on the one hand, confirmed the reliability of the molecular modeling results; on the other hand, it pointed out that OPD and OPD′ can affect the transporting activities of OATP1B1 and OATP1B3 in a substrate-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…In another article we submitted, molecular modeling was adopted and screen out a protein called Q9NPD5 which can interact with both OPD and OPD'. This protein belongs to organic anion transporters (OATP) family and it was closely related to cholic acid metabolism [ 28 ], existing studies have confirmed that the down-regulation of OATP1A2 and OATP1B3 in particular leads to abnormal fetal bile acid metabolism between maternal and fetal fetuses [ 29 ]. This may explain from another perspective how OPD and OPD' induce hemolysis.…”
Section: Discussionmentioning
confidence: 99%